Dual Role of Exosome in Neurodegenerative Diseases: A Review Study - Sheykhhasan, Mohsen; Heidari, Fatemeh; Farsani, Mohsen Eslami; Azimzadeh, Maryam; Kalhor, Naser; Ababzadeh, Shima; Seyedebrahimi, Reihaneh (Current stem cell research & therapy, 2024)
Extracellular vesicles (EVs) are one of the crucial means of intercellular communication, which takes many different forms. They are heterogeneous, secreted by a range of cell types, and can be generally classified into microvesicles and exosomes depending on their location and function. Exosomes are small EVs with diameters of about 30-150 nm and diverse cell sources. The MEDLINE/PubMed database was reviewed for papers written in English and publication dates of recent years, using the search string "Exosome" and "Neurodegenerative diseases." The exosomes have attracted interest as a significant biomarker for a better understanding of disease development, gene silencing delivery, and alternatives to stem cell-based therapy because of their low-invasive therapeutic approach, repeatable distribution in the central nervous system (CNS), and high efficiency. Also, they are nanovesicles that carry various substances, which can have an impact on neural plasticity and cognitive functioning in both healthy and pathological circumstances. Therefore, exosomes are conceived as nanovesicles containing proteins, lipids, and nucleic acids. However, their composition varies considerably depending on the cells from which they are produced. In the present review, we discuss several techniques for the isolation of exosomes from different cell sources. Furthermore, reviewing research on exosomes' possible functions as carriers of bioactive substances implicated in the etiology of neurodegenerative illnesses, we further examine them. We also analyze the preclinical and clinical research that shows exosomes to have therapeutic potential.